Fibrinogen and α1-antitrypsin in COPD exacerbations. Issue 11 (24th August 2015) - Ingebrigtsen, Truls S; Marott, Jacob L; Rode, Line; Vestbo, Jørgen; Lange, Peter; Nordestgaard, Børge G
Abstract : Background: We tested the hypotheses that fibrinogen and α1 -antitrypsin are observationally and genetically associated with exacerbations in COPD. Methods: We studied 13 591 individuals with COPD from the Copenhagen General Population Study (2003–2013), of whom 6857 were genotyped for FGB -455 (rs1800790, G>A) and FGB -448 (rs4220, G>A) and had plasma fibrinogen measured. Furthermore, 13 405 individuals were genotyped for the SERPINA1 S-allele (rs17580) and the Z-allele (rs28929474) and had measurements of plasma α1 -antitrypsin. Exacerbations were defined as hospital admissions or treatments with systemic corticosteroids. We studied observational associations between plasma measurements and exacerbations in Cox regression analyses, associations between genotypes and exacerbations in logistic regression analyses and associations between genetically determined plasma levels and exacerbations in instrumental variable analyses. Results: Elevated fibrinogen and α1 -antitrypsin levels were associated with increased risk of exacerbations in COPD, HR=1.14 (1.07 to 1.22, p<0.001) and 1.18 (1.11 to 1.25, p<0.001), respectively, per SD increase. Presence of the Z-allele was associated with increased odds of exacerbations, OR=1.25 (1.05 to 1.48, p=0.01), as was α1 -antitrypsin level genetically lowered by the Z-allele, OR=1.07 (1.02 to 1.13, p=0.004), per SD decrease. Fibrinogen elevating genotypes, FGB -455 (AA) and FGB -448 (AA), were not associated with exacerbations, OR=0.96 (0.73 to 1.25, p=0.77) and OR=1.01 (0.75 to 1.33, p=0.90), respectively, and neither was genetically elevated fibrinogen level, OR=1.11 (0.76 to 1.63, p=0.58) per SD increase. Conclusions: Fibrinogen and α1 -antitrypsin were observationally associated with increased risk of exacerbations. However, genetically, fibrinogen per se was not associated with exacerbations, while lowered α1 -antitrypsin was associated with increased odds of exacerbations.